(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article investigates the theoretical and methodological underpinnings of Qira’at (Quranic recitations) within the broader framework of Tafsir (exegesis). It analyzes the historical trajectory of Quranic codification, beginning with the foundational efforts of Caliph Uthman ibn Affan and progressing through the scholarly contributions of Ibn Mujahid, Al-Shatibi, and Ibn al-Jazari. The study identifies five pivotal stages of canonization that transformed the oral tradition into a standardized academic discipline. Furthermore, it explores the integration of recitation variants in classical exegetical works, such as those by Al-Tabari, Al-Zamakhshari, and Al-Nasafi, highlighting how these variants influence legal and linguistic interpretations in Islamic scholarship.